2009
DOI: 10.1124/mol.109.055137
|View full text |Cite
|
Sign up to set email alerts
|

Heme-Oxygenase-1 Induction and Carbon Monoxide-Releasing Molecule Inhibit Lipopolysaccharide (LPS)-Induced High-Mobility Group Box 1 Release in Vitro and Improve Survival of Mice in LPS- and Cecal Ligation and Puncture-Induced Sepsis Model in Vivo

Abstract: We examined our hypothesis that heme-oxygenase-1 (HO-1)-derived carbon monoxide (CO) inhibits the release of highmobility group box 1 (HMGB1) in RAW264.7 cells activated with lipopolysaccharide (LPS) in vitro and in LPS-or cecal ligation and puncture (CLP)-induced septic mice in vivo, so that HO-1 induction or CO improves survival of sepsis in rodents. We found that pretreatment with HO-1 inducers (hemin, cobalt protoporphyrin IX) or transfection of HO-1 significantly inhibited HMGB1 release, which was blocked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
110
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(124 citation statements)
references
References 37 publications
9
110
1
Order By: Relevance
“…In contrast, enhanced induction of HO-1 and the administration of CORM-2 inhibit thrombus formation and affect the protein C system in sepsis [38]. CORM-2 reduces HMGB1 release in macrophages and septic animal models [9,39]. Our study showed that CORM-2 moderates TNF-α-induced TF and PAI-1 up-regulation.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In contrast, enhanced induction of HO-1 and the administration of CORM-2 inhibit thrombus formation and affect the protein C system in sepsis [38]. CORM-2 reduces HMGB1 release in macrophages and septic animal models [9,39]. Our study showed that CORM-2 moderates TNF-α-induced TF and PAI-1 up-regulation.…”
Section: Discussionmentioning
confidence: 58%
“…Numerous reports have demonstrated CO-dependent protection in animal models of inflammatory syndromes, including sepsis [9] and colitis [10]. Inhalation of CO significantly suppresses ischemic induction of PAI-1 expression and the accumulation of fibrin in mice [11].…”
Section: Introductionmentioning
confidence: 99%
“…CO may effectively interact with several intracellular heme-containing targets (e.g., soluble guanylate cyclase, cytochrome c oxidase, NADPH oxidase, potassium channels) to transduce important signals within cells. Several studies demonstrated that CO derived from CORMs can protect mice from lethal endotoxemia and polymicrobial sepsis induced by CLP (28,(70)(71)(72)(73). Recently, CORMs have been described to exert bactericidal (CORM-2, -3) or bacteriostatic (CORM-A1) activities against P. aeruginosa growth in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…We first showed direct evidence that acteoside contributes to the reduction of HMGB1 and NO production by inducing HO-1 in macrophages. Other studies suggested that HMGB1 mediates cognitive impairment in sepsis survivors (Chavan et al, 2012;Huang et al, 2010) and that HO-1 inhibits the release of HMGB1 in Raw264.7 cells activated by LPS and in LPS-or CLP-induced septic mice (Tsoyi et al, 2009). Next, we assessed the signaling pathway through which acteoside induces HO-1.…”
Section: Discussionmentioning
confidence: 92%
“…Anti-HMGB1 antibodies and HMGB1 inhibitors significantly improve survival in septic animals, suggesting that HMGB1 is a possible therapeutic target in sepsis (Barnay-Verdier et al, 2011;Sama et al, 2004). Heme oxygenase-1 (HO-1), a stress-responsive protein induced by stimulants (inflammatory cytokines, heat shock, heavy metals, and oxidants) (Jang et al, 2012;Tsoyi et al, 2009) decreases circulating HMGB1 levels in animal models of sepsis and improves patient survival, demonstrating its therapeutic potential in inflammatory disorders . In addition, it is well known that the inducers of HO-1 expression inhibits the expression of the inflammatory genes (cyclooxygenase-2 and inducible nitric oxide synthase), and subsequently decreases PGE 2 and NO production (Oh et al, 2006;Suh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%